High Suppressor of Cytokine Signaling-3 Expression Impairs STAT3-dependent Protective Effects of Interleukin-22 in Ulcerative Colitis in Remission. Issue 2 (February 2015) - Xu, An Tao; Li, Yi; Zhao, Di; Shen, Jun; Xu, Xi Tao; Qiao, Yu Qi; Zhu, Ming Ming; Wang, Tian Rong; Cui, Yun; Ai, Luo Yan; Ran, Zhi Hua
Abstract : Background: High SOCS3 expression in intestinal epithelial cells (IECs) of patients with ulcerative colitis (UC) in remission reflects the shorter time to relapse. We investigated whether high SOCS3 increased risk for relapse through violating STAT3-dependent protective effects of interleukin (IL)-22 during UC remission. Methods: Expression of IL-22 and c-Myc in UC remission mucosa was analyzed by immunohistochemistry. Effects of IL-22 on migration and proliferation of IEC cell lines with enforced SOCS3 expression were assessed with wounding assay and CCK-8 assay, respectively. Influence of STAT3 interference and SOCS3 overexpression on IL-22–regulated expression of antimicrobial peptide and proliferation-related molecules, including DMBT1, c-Myc, Survivin, Bcl-2, and Bcl-xL, were performed with quantitative real-time polymerase chain reaction or Western blot. Results: Patients with UC in remission showed significantly more IL-22–positive immune cells, but no difference of epithelial c-Myc levels, in mucosa compared with healthy controls. Overexpression of SOCS3 nearly abolished IL-22–induced activation of STAT3. By inhibiting STAT3 signaling, SOCS3 influenced IL-22–induced expression of DMBT1, c-Myc, Survivin, and Bcl-2 as well as proliferation and migration processes in cultured IEC cell line. Conclusions: SOCS3 overexpression impairs IL-22–mediated epithelial homeostasis and mucosal wound healing, which could be the mechanism for high SOCS3 IEC expression contributed early relapse of mucosal inflammation. Prevention of SOCS3 expression or enhancement of IL-22/STAT3 signaling in IEC seems to be rational therapeutic strategies for UC remission maintenance. Abstract : Article first published online 24 December 2014.